SEMIOTICS OF PRINT MATERIALS: HOW GRAPHICS “SPEAK” THROUGH SYMBOLS - Trehubov, Kostiantyn (Theory and practice of design, 2025)
Purpose. The article explores the semiotic mechanisms behind the functioning of graphic elements in printed materials. It aims to identify how visual signs, such as color, typography, composition, and iconic imagery, operate as carriers of meaning in the context of visual communication and design. The objective is to outline the cultural codes, symbolic structures, and cognitive processes involved in the perception of print graphics. Methodology. The study employs an interdisciplinary approach, integrating classic and post-classic semiotic theory with contemporary visual communication studies. It applies comparative, structural, and cultural analysis to a selection of print media from Ukrainian and global design practices. Results. The analysis confirms that printed design elements fulfill a dual function – communicative and symbolic. Each graphic component – color, shape, font, spatial arrangement – acts as a sign within a complex system of visual language. Using Peirce’s semiotic model (icon, index, symbol), the paper classifies graphic signs and analyzes their interpretative potential in a culturally conditioned environment. The interaction between verbal and visual codes creates rich, multilayered meanings that influence viewer perception. Scientific novelty. The paper offers a comprehensive perspective on print design as a semiotic system. It provides original insights into how symbols, conventions, and cultural archetypes are encoded in visual communication. The novelty lies in the integration of semiotic principles with the practical aspects of graphic and print design, especially within the Ukrainian context. Practical relevance. The findings can be applied in design practice, branding, publishing, advertising, and communication strategies. The methods outlined may serve as a foundation for design education, providing future designers with tools for constructing culturally resonant and semiotically effective visual messages.